A pilot study of Aboriginal health promotion from an ecological perspective - van den Tol Gemma (BMC Public Health, 2011)
Abstract Background For health promotion to be effective in Aboriginal and Torres Strait Islander Communities, interventions (and their evaluation) need to work within a complex social environment and respect Indigenous knowledge, culture and social systems. At present, there is a lack of culturally appropriate evaluation methods available to practitioners that are capable of capturing this complexity. As an initial response to this problem, we used two non-invasive methods to evaluate a community-directed health promotion program, which aimed to improve nutrition and physical activity for members of the Aboriginal community of the Goulburn-Murray region of northern Victoria, Australia. The study addressed two main questions. First, for members of an Aboriginal sporting club, what changes were made to the nutrition environment in which they meet and how is this related to national guidelines for minimising the risk of chronic disease? Second, to what degree was the overall health promotion program aligned with an ecological model of health promotion that addresses physical, social and policy environments as well as individual knowledge and behaviour? Methods Rather than monitoring individual outcomes, evaluation methods reported on here assessed change in the nutrition environment (sports club food supply) as a facilitator of dietary change and the 'ecological' nature of the overall program (that is, its complexity with respect to numbers of targets, settings and strategies). Results There were favourable changes towards the provision of a food supply consistent with Australian guidelines at the sports club. The ecological analysis indicated that the design and implementation of the program were consistent with an ecological model of health promotion. Conclusions The evaluation was useful for assessing the impact of the program on the nutrition environment and for understanding the ecological nature of program activities.